Susceptibility of Staphylococcus aureus Isolated from Different Raw Meat Products to Disinfectants - Fatma Özdemir; Seza Arslan (European Journal of Biology)
Objective: Staphylococcus aureus, a severe public health hazard, causes foodborne diseases from the consumption of contaminated food. Various antimicrobials and disinfectants are used throughout the food chain to reduce microbial contamination or eliminate microorganisms on food contact surfaces. However, little is known about the susceptibility of disinfectants to food pathogens, including S. aureus, which can develop resistance to antimicrobials and cause severe diseases. Materials and Methods: The antimicrobial activity of triclosan, cetyltrimethylammonium bromide (CTAB), acetic acid, citric acid, and lactic acid against 50 S. aureus isolates, including multidrug-resistant (MDR) isolates originating from ground beef, chicken, and fish, was investigated using the broth microdilution method. Results: The minimal inhibitory concentrations (MICs) of triclosan, CTAB, acetic acid, citric acid, and lactic acid against the isolates were 0.125-16 μg/mL, 0.25-32 μg/mL, 102.5-26250 μg/mL, 187.5-12000 μg/mL, and 703-22500 μg/mL, respectively. Almost all MDR isolates showed resistance to triclosan. There was a statistically significant difference in MICs between triclosan and organic acids, as well as between CTAB and organic acids (p < 0.05). However, a statistically significant difference was not observed in triclosan and CTAB, as well as in acetic acid and lactic acid (p > 0.05). Pearson correlation coefficient revealed a strong relationship between triclosan and multidrug resistance. Based on the multiple linear regression analysis, triclosan had a positive effect on multidrug resistance (p < 0.05). Conclusion: This research gives helpful information on the susceptibility of disinfectants to S. aureus, particularly to resistant S. aureus isolates from meats, which may help to recommend proper disinfectant use in food production.